The method of terms transformation of linguistic variables in decision-making analysis and information security risk assessment - Казмирчук, Светлана Владимировна (Ukrainian Information Security Research Journal, 2013)
One of the stages to develop a complex data protection system and Information Security Management System (ISMS) is provided by implementing the process of analysis and risk assessment. In relevant systems, when assessing die fuzzy conditions to interpret a natural language descriptions the linguistic variables with a certain number of terms that appear fuzzy numbers are used. In practical use of mentioned systems, there are situations when it is convenient for analysis and risk assessment, to apply standards with die ability to vary the number of terms. For this purpose the redefinition of die specified standards without participation of experts is necessary. A solution for this task is the offered method which provides an analytical function and enables to transform (die equivalent conversion) more terms of linguistic variables to less. Such approach will enhance die flexibility of developed assessment techniques based on die logical and linguistic approach and use to describe die linguistic variable die trapezoid and triangular fuzzy numbers.